ENGLISH TEACHERS’ PERCEPTION OF TEACHING VOCABULARY DURING ONLINE LEARNING IN THE COVID-19 PANDEMIC - Andriyati, Anisa; Kusrin, Kusrin; Yanto, Elih Sutisna (IKIP Siliwangi, 2022)
The objective of this research was to investigate English teachers' perceptions about teaching vocabulary during online learning in the COVID-19 Pandemic at junior high school. This research provides one research question: What is English teachers’ perception about teaching vocabulary online learning? The study was conducted by using qualitative research as the research design. The participants of this study were the English teacher at Islamic Junior High School in Telukjambe Timur Karawang. The instruments used in this study were semi-structure interview for teachers. The findings of this study found three main themes regarding to the English Teachers’ Perception about Teaching Vocabulary During Online Learning in the COVID-19 Pandemic: (1)The advantage of teaching vocabulary online learning during the COVID-19 Pandemic, (2)The challenges of teaching vocabulary online learning during the COVID-19 Pandemic, (3)The innovation and strategy of teaching vocabulary online learning during the COVID-19 Pandemic. The result implies that the teachers had positive view of vocabulary online learning during the COVID-19 pandemic, students become easier, practical to be able to understand and follow vocabulary learning online because surely every English teacher will more creative to provide vocabulary learning materials through either from a video, picture that has been prepared complete with visual images along with clear writing and sound through various technological media (Google Classroom, Google Meet, E-learning, Youtube, WhatsApp etc.) that English teachers have learned before. Keywords: English Teachers, Perception, Online Learning, Teaching Vocabulary, COVID-19